Modelando el problema de la informalidad empresarial - Fernández, José Sergio; Saez Mosquera, Inty; Redchuk, Andrés (My University, 2014)
One of the biggest problems to face the study of informality is the uncertainty that has characterized its conceptualization. However, the common position of most government is trying to eradicate the manifestation of this phenomenon, affecting both developed and underdeveloped or developing countries. The traditional policy of enforcement by the government have proven today its high infectivity, although the continuing debate about the theoretical conceptualization of the problem, in this paper we propose, without trying to close the discussion, summarize the findings derived from an economic model, the main features of the operation of economic informality -genuine manifestation as we consider, assumed as an adaptive response to the economic systems the way they are conducted and measured.

Uno de los mayores problemas al encarar el estudio de la informalidad es la imprecisión que ha caracterizado su conceptualización. Sin embargo, la posición común de la mayoría de los estados es intentar erradicar la manifestación de este fenómeno, que afecta tanto a países desarrollados como a subdesarrollados o en vías de desarrollo. Las tradicionales políticas de enforcement por parte de los estados han comprobado a día de hoy su elevada inefectividad, y aunque continua el debate en torno a la conceptualización teórica del problema, en este artículo proponemos –sin pretender cerrar el debate, resumir a partir de las conclusiones derivadas de un modelo económico, las principales características del funcionamiento de la informalidad como manifestación económica que consideramos genuina, en tanto la asumimos como una respuesta adaptativa de los sistemas económicos a la forma en que son conducidos y medidos.
El caso de la Provincia del Chaco en Argentina
Keywords: informality; social cost of informality; productive disparity; informalidad empresarial; costo social de la informalidad; disparidad productiva